2021
DOI: 10.1038/s41598-021-83070-x
|View full text |Cite
|
Sign up to set email alerts
|

Pupil dilation reflects the authenticity of received nonverbal vocalizations

Abstract: The ability to infer the authenticity of other’s emotional expressions is a social cognitive process taking place in all human interactions. Although the neurocognitive correlates of authenticity recognition have been probed, its potential recruitment of the peripheral autonomic nervous system is not known. In this work, we asked participants to rate the authenticity of authentic and acted laughs and cries, while simultaneously recording their pupil size, taken as proxy of cognitive effort and arousal. We repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 81 publications
2
17
0
Order By: Relevance
“…Importantly, when we explored the simple effects of authenticity on ERP amplitudes for laughter and crying separately, we observed that the main effect on N100 was driven by the simple effect in crying, and the one on P200 by the simple effect in laughter (both effects being statistically significant). This evidence converges with the pupillometry evidence we have recently published from roughly the same sample of participants 64 , collected during the same experimental session. Therein, we observed a similar pattern of difference between laughter and crying.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Importantly, when we explored the simple effects of authenticity on ERP amplitudes for laughter and crying separately, we observed that the main effect on N100 was driven by the simple effect in crying, and the one on P200 by the simple effect in laughter (both effects being statistically significant). This evidence converges with the pupillometry evidence we have recently published from roughly the same sample of participants 64 , collected during the same experimental session. Therein, we observed a similar pattern of difference between laughter and crying.…”
Section: Discussionsupporting
confidence: 91%
“…Still, what drives salience attribution to non-authentic emotional vocalisations in the first place needs to be further narrowed down. We also suggest that what drives the early stages of authenticity recognition in crying and laughter might not be the same—with the former achieved through arousal, and the latter through a higher-order cognitive processing, en par with our pupillometry findings 64 . In sum, the current study—being the first to investigate authenticity recognition using EEG—hopefully serves as a driver of new hypotheses and independent studies—which will be helpful to substantiate the novel findings presented here.…”
Section: Conclusion and Further Researchmentioning
confidence: 54%
See 2 more Smart Citations
“…Pupil amplitude artifacts (<1 or >9 mm), as well as drifts and blinks, were coded as missing values ( Rosa et al, 2015 ). Pupil diameters of zero lasting between 100 and 600 ms were considered blinks ( Cosme et al, 2021 ), and replaced using linear interpolation ( Carvalho and Rosa, 2020 ). Finally, a seven-point weighted average filter was applied to smooth data.…”
Section: Methodsmentioning
confidence: 99%